Access to daylight and view in an office improves cognitive performance and satisfaction and reduces eyestrain: A controlled crossover study. (November 2019) - Jamrozik, Anja; Clements, Nicholas; Hasan, Syed Shabih; Zhao, Jie; Zhang, Rongpeng; Campanella, Carolina; Loftness, Vivian; Porter, Paige; Ly, Shaun; Wang, Selena; Bauer, Brent
Abstract: Windows provide access to daylight and view, both of which have been linked to positive outcomes for occupants, including improved satisfaction, well-being, and performance. However, window access can also cause discomfort and eyestrain from glare. This controlled crossover study tested the occupant impacts of two modern shading systems designed to provide daylight and view while minimizing glare: windows with manually-controlled motorized mesh shades (Mesh Shades) and windows with automatic tinting (Dynamic Tint). Ten participants spent fourteen weeks working in a living lab in which three conditions were non-consecutively repeated for two-week periods: Mesh Shades, Dynamic Tint, and a baseline condition lacking daylight and view (Blackout Shades). Participants' cognitive function performance, satisfaction, and eyestrain in the baseline Blackout Shades condition were compared to the same measures in the Mesh Shades and Dynamic Tint conditions. Two aspects of cognitive function performance—Working Memory and Inhibition—improved in both the Mesh Shades and Dynamic Tint conditions. Satisfaction with light as well as with the overall environment improved in both the Mesh Shades and Dynamic Tint conditions. Eyestrain symptoms were reduced in both the Mesh Shades and Dynamic Tint conditions. There were no statistical differences between settings with Dynamic Tint and motorized Mesh Shades on measures of cognitive function performance, satisfaction, or eyestrain symptoms. This research demonstrates that providing access to daylight and view in an office environment using modern shading methods can improve occupants' cognitive performance and satisfaction while reducing eyestrain. Highlights: Modern shading methods can provide daylight and view while limiting glare. Controlled crossover study tested occupant impacts of two shading methods in office. Participants worked in living lab for 14 weeks while three conditions were repeated. Outcomes in two shading conditions compared to baseline lacking daylight or view. Cognitive performance, satisfaction, and eyestrain improved in shading conditions.